2018
DOI: 10.11113/jt.v81.10468
|View full text |Cite
|
Sign up to set email alerts
|

RHIZOPHORA MANGLE L. LEAF BIOCHEMICAL CHARACTERIZATION: NATURAL-GREEN TOTAL-CORROSION INHIBITION PROSPECT ON CONCRETE STEEL-REINFORCEMENT IN 3.5% NaCl

Abstract: Effective corrosion-protection by plant-extract on metals, in aggressive service-environment, is dependent on the biochemical constituents of which the natural plant is made-up. This paper investigates biochemical characterization of inorganic and organic constituents of Rhizophora mangle L. leaf for gaining insight on its steel-reinforcement corrosion mitigating prospect in NaCl-immersed concretes. For the study, atomic absorption spectroscopy (AAS), Fourier transform infrared spectroscopy (FT-IR) and phytoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…ts from the Kolmogorov-Smirnov goodness-of-fit test-applications for the fittings of the corrosion datasets to the Normal and the Weibull probability distribution functions. Also (2) ), and variations from such Normal and Weibull , the reliability of the obtained expected values followed from their respective (3) (4) ,of corrosion tests, like the Smirnov goodness-of-fit (5) concentrations was assessed of better-fit of the scatter (%), according to: [48][49][50][51][52][53][54] (6) electrochemical measurements of corrosion rate using the Normal the plots of Normal ), of obtaining each mean…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ts from the Kolmogorov-Smirnov goodness-of-fit test-applications for the fittings of the corrosion datasets to the Normal and the Weibull probability distribution functions. Also (2) ), and variations from such Normal and Weibull , the reliability of the obtained expected values followed from their respective (3) (4) ,of corrosion tests, like the Smirnov goodness-of-fit (5) concentrations was assessed of better-fit of the scatter (%), according to: [48][49][50][51][52][53][54] (6) electrochemical measurements of corrosion rate using the Normal the plots of Normal ), of obtaining each mean…”
Section: Resultsmentioning
confidence: 99%
“…-2, that increase in the C 6 H 18 N 4 admixture concentration in the steel-reinforced concrete samples for the H 2 SO 4 medium leads to increase in the corrosion-inhibition efficiency. [55][56][57] Further analyses of this performance model by the C 6 H 18 N 4 admixture, via probing of mathematical correlation modeling, 35,46,49,58 as per ASTM G16-13(2019), 36 indicated that the inhibition efficiency, η (%), exhibited a relationship with the C 6 H 18 N 4 concentration, ρ (M), which could be represented as:…”
Section: Corrosion Inhibition Performance Model Computationmentioning
confidence: 99%
“…As a further matter, there is a growing appeal for developing different green-based corrosion inhibitors acquired from plant extracts in combating the corrosion of reinforced steel in concrete structures because of the less toxic and biodegradable nature of the extracts [11,[16][17][18][19][20]. Studies reported that the suitability of the N-, S-, and O-containing and π electron-rich leaves extracts of Phyllanthus muellerianus [18], Chamaerops humilis L. [20], and Olea europaea [21] acted as an effective anticorrosion agent for reinforcing steel in concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicated that R. mangle L. bark-extract is rich in tannins [47, 48, 51], from which it could be noted that tannins from Rhizophora apiculata ( R. apiculata ), a plant sharing same Rhizophoraceae taxonomical family, have been reported as effective inhibitor of steel corrosion [5254]. Also, recent scientific journals [55, 56] via collaborative work by authors of this study with other researchers, have detailed that R. mangle L. leaf-extract and R. mangle L. bark-extract are constituted of lone-pairs/ π -electron rich, organic, biochemical compounds [45]. The constitution of the biochemical compounds detailed in [55, 56] in the leaf and bark of R. mangle L. portend corroborations for the positive performances exhibited by the extracts on the inhibition of reinforcing-steel corrosion in sulphuric acid-immersed concrete [57–61].…”
Section: Introductionmentioning
confidence: 99%
“…Also, recent scientific journals [55, 56] via collaborative work by authors of this study with other researchers, have detailed that R. mangle L. leaf-extract and R. mangle L. bark-extract are constituted of lone-pairs/ π -electron rich, organic, biochemical compounds [45]. The constitution of the biochemical compounds detailed in [55, 56] in the leaf and bark of R. mangle L. portend corroborations for the positive performances exhibited by the extracts on the inhibition of reinforcing-steel corrosion in sulphuric acid-immersed concrete [57–61]. However, while R. mangle L. leaf-extract has also been applied for effectively inhibiting reinforcing-steel corrosion in NaCl-immersed concrete [62, 63], no study have used R. mangle L. bark-extract for corrosion-inhibition of steel-rebar in this medium.…”
Section: Introductionmentioning
confidence: 99%